Graphene‐Based Magnetocaloric Composites for Energy Conversion. Issue 1 (6th October 2022) - Coppi, Chiara; Cugini, Francesco; Magnani, Giacomo; Milanese, Chiara; Nasi, Lucia; Lazzarini, Laura; Pontiroli, Daniele; Riccò, Mauro; Solzi, Massimo
Abstract : Herein, a simple, versatile, and cost‐effective method to fabricate innovative thermal conductive magnetocaloric (MC) composites, which offers a smart solution to manufacture active elements with desired geometries, overcoming the current thermal and mechanical limits of the most studied MC materials, is presented. The composite is prepared by embedding powder of a MC material in an epoxy matrix enriched with a graphene‐based material, obtained by thermal exfoliation of graphite oxide. The graphene‐enriched composite shows a significant improvement of the MC time response to the magnetic field, due to the formation of a 3D network that bridges the MC particles and reduces the metal–matrix contact resistance, thus creating a percolation path for an efficient heat transfer. Because of the simplicity and scalability of the preparation method and the great enhancement in response time, these new functional composites represent an important step for the effective application of MC materials in thermomagnetic devices for the energy conversion. Abstract : Herein, a simple, versatile, scalable, and cost‐effective method to prepare innovative epoxy‐based MC composites, enriched with a graphene‐based material obtained by thermal exfoliation of graphite oxide, is presented. The fast MC response, high formability, and good mechanical properties make these composites a smart and promising solution to manufacture active elements for thermomagnetic energy conversion technologies.